(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Nowadays, a lot of waste glass produced through different sides of life. Applying sustainability has been widely used in different construction materials and flexible pavement was contained different recycled materials through different studies. Recycled glass, where it is nonmetallic and inorganic, it can neither be incinerated nor decomposed, so it may be difficult to reclaim, has been used as filler, fine and coarse aggregates in the asphalt base course. In this study, various standard asphalt tests, such as stability, flow, density and air voids, have been conducted on reference mix asphalt and mix asphalt with different percentages of recycled glass when it has been used as filler, fine and coarse aggregates in the base course. Generally, the results show good indication, especially when using 10% of the recycled glass instead of coarse aggregate with 40-50 asphalt grades. This percentage improves most characteristics such as strength retained index which indicates better performance than reference mix.